Atomic-resolution mapping of transcription factor-DNA interactions by femtosecond laser crosslinking and mass spectrometry - Alexander Reim (Nature Portfolio, 2020)
Cross-linking mass spectrometry (MS) is an important tool in structural biology, but its application to protein-DNA complexes has been hampered by low cross-linking efficiency. Here, the authors develop a femtosecond UV-laser induced cross-linking MS workflow to map protein-DNA interactions in vitro and in cells.